(untitled) (Altre Modernità, 2011)
The graphic report published in 2006 by Sid Jacobson and Ernie Coln, an adaptation from The 9/11 Report by the National Commission on terrorist attacks upon the United States, was dedicated “to the memory of those who lost their lives”, hoping that it could help to better understand what happened that day and in the years leading up to it. Thus, using the rhetoric of terror as a guideline, memory seems to be the central aim of a book which longs to be “accessible to all”, in particular, to a new set of readers who could be interested in graphic narration. “Our goal (…) was not only to inform our fellow citizens about history but also to energize and engage them on behalf of reform and change, to make our country safer and more secure”, so reads the Forward to Jacobson and Coln’s work. But is it true?